The use of microelectrodes with AGNES - Huidobro, C. (2013)
Absence of gradients and nernstian equilibrium stripping (AGNES) is a new electroanalytical technique designed to determine free heavy metal ion concentrations in solutions. AGNES had been applied, up to date, with conventional equipment such as the hanging mercury drop electrode (HMDE). Due to their much smaller volume, microelectrodes can reach a given preconcentration factor within a much shorter deposition time, so their use for AGNES has been evaluated in this work. For the particular case of the mercury microelectrode deposited onto an Ir disk (radius around 5 lm), AGNES has been successfully used for speciation purposes in the system Pb + PDCA (pyridinedicarboxylic acid). However, due to a relatively large capacitive current, which decays slowly, the limit of quantification for such microelectrodes has only been reduced by one half with respect to that of the HMDE.